Review of Visualizing the Pyramids - Anderson, David A..
Peter Der Manuelian, Visualizing the Pyramids. Harvard University Press, Cambridge Massachusetts. 2017. ISBN : 9780674731233. 255 pages, 100+ color and black and white illustrations.